Risk of Cardiovascular Morbidity in Patients With Psoriatic Arthritis: A Meta‐Analysis of Observational Studies. Issue 1 (27th December 2016) - Polachek, Ari; Touma, Zahi; Anderson, Melanie; Eder, Lihi
Abstract : Objective: To assess the magnitude of risk of cardiovascular and cerebrovascular morbidity in patients with psoriatic arthritis (PsA) compared with the general population through a systematic review and meta‐analysis of observational studies. Methods: We searched the Medline, Embase, and Cochrane databases, as well as abstracts archives from rheumatology conferences. Observational studies that included a PsA diagnosis, cardiovascular or cerebrovascular outcomes, and a comparison group of individuals without psoriasis and rheumatic diseases and were case–control, cross‐sectional, or cohort studies, were assessed by 2 researchers. We calculated weighted pooled summary estimates of the maximally adjusted effect size estimates for cardiovascular and cerebrovascular diseases using the random‐effects model, and tested for heterogeneity using the I 2 statistic. Results: Eleven studies, comprising 32, 973 patients with PsA, met the inclusion criteria. There was a 43% increased risk of cardiovascular diseases in patients with PsA compared with the general population (pooled odds ratio [OR] 1.43 [95% confidence interval (95% CI) 1.24–1.66]). The risk of incident cardiovascular events was increased by 55% (pooled OR 1.22–1.96). Morbidity risks for myocardial infarction, cerebrovascular diseases, and heart failure were increased by 68%, 22%, and 31%, respectively (pooled OR 1.68 [95% CI 1.31–2.15], pooled OR 1.22 [95% CI 1.05–1.41], and pooled OR 1.31 [95% CI 1.11–1.55], respectively). We identified significant heterogeneity in all main analyses ( P  < 0.001). Conclusion: Cardiovascular and cerebrovascular morbidity are increased by 43% and 22%, respectively, in patients with PsA compared with the general population.